Changes in Trust after Driving Level 2 Automated Cars. (5th August 2018) - Walker, Francesco; Boelhouwer, Anika; Alkim, Tom; Verwey, Willem B.; Martens, Marieke H.
Abstract : Overtrust and undertrust are major issues with partially automated vehicles. Ideally, trust should be calibrated ensuring that drivers' subjective feelings of safety match the objective reliability of the vehicle. In the present study, we examined if drivers' trust toward Level 2 cars changed after on-road experience. Drivers' self-reported trust was assessed three times: before having experience with these vehicles, immediately after driving two types of vehicles, and two weeks after the driving experience. Analysis of the results showed major changes in trust scores after the on-road driving experience. Before experiencing the vehicles, participants tended to overestimate the vehicle capabilities. Afterwards they had a better understanding of vehicles' limitations, resulting in better calibrated trust.